Calculating the economic burden of fatal drowning in Australia. (December 2018) - Barnsley, Paul D.; Peden, Amy E.; Scarr, Justin
Abstract: Background: Aquatic activities provide physical and social benefits, while the risk of drowning generates countervailing social costs. Drawing on estimates of fatal drowning gathered by Royal Life Saving Society – Australia, this paper outlines a method for estimating the economic burden attributable to fatal drowning. Methods: This study estimated the burden of fatal drowning by combining Value of a Statistical Life Year (VSLY), hospitalization, productivity and emergency services costs. All unintentional fatal drowning cases in Australia between 1-July-2002 and 30-June-2017 were included. Foregone life years from each drowning were estimated based on Australian life expectancies for the year of death. The societal value of these Years of Life Lost was calculated using the VSLY for Australia, adjusted to reflect income elasticity. Corrections to discounting of VSLY were applied. Estimates of productivity losses not captured in VSLY were produced using net national capital growth. Time spent in hospital was found using coronial data and existing estimates of search, ambulance and coronial costs were adapted and incorporated. Results: The study covers 4285 cases of unintentional fatal drowning over 15 years. Based on this sample and estimates for the VSLY (203, 000), the economic burden of fatal drowning for Australia over this 14 year period was 18.63 billion in 2017 Australian dollars, averaging 1.24 billion annually. Conclusions: Fatal drowning represents a significant source of health burden in Australia, underlining the need for further preventative measures. Practical applications: We provide an easily-understood estimate of the scale of Australia's fatal drowning problem, permitting comparison with other social problems. They can also be used in determining net benefits of proposed drowning prevention policies and to identify situations where burden of fatal drowning is disproportionate. Suggestions for improving the calculation of societal burden of illness can be incorporated in cost-benefit analyses in related fields of study. Highlights: We provide a scale estimate of Australia's fatal drowning problem, allowing comparison with other social problems. Burden estimates can be used in determining net benefits of proposed drowning prevention policies. Estimates of burden by demographic group and location enable identification of disproportionate burdens of fatal drowning. Improvements to the calculation of burden of illness can be incorporated in cost-benefit analyses in related fields.